Micropuncture technique for femoral access is associated with lower vascular complications compared to standard needle. Issue 7 (16th October 2020) - Ben‐Dor, Itsik; Sharma, Avinash; Rogers, Toby; Yerasi, Charan; Case, Brian C.; Chezar‐Azerrad, Chava; Musallam, Anees; Forrestal, Brian J.; Zhang, Cheng; Hashim, Hayder; Bernardo, Nelson; Satler, Lowell F.; et al.
Abstract: Objectives: We compared access‐site complications with a Micropuncture 21‐gauge (G) needle to a standard 18G needle in patients undergoing femoral‐access percutaneous coronary intervention (PCI). Background: Vascular access‐site complications are the most common complication after cardiac catheterization. These complications increase patient morbidity and mortality, along with healthcare costs. Methods: We retrospectively analyzed a cohort of 17, 844 consecutive patients undergoing PCI. Micropuncture access was used in 2344 patients and a standard 18G needle in 15, 500 patients. Primary endpoints included vascular perforation or limb ischemia requiring repair, retroperitoneal bleeding, pseudoaneurysm, arteriovenous fistula, groin hematoma (>4 cm). Results: Patients undergoing PCI with Micropuncture were at higher risk: they were on anticoagulation (557 [23.7%] vs. 1, 590 [10.2%], p < .001), used steroids more frequently (131 [5.6%] vs. 638 [4.1%], p < .001) and required the use of an intra‐aortic balloon pump more often (191 [(8.1%] vs. 896 [5.7%], p < .001). Overall, the access‐site complications rate was lower using Micropuncture (58 [2.5%]) versus standard needle (558 [3.6%], p = .005). The Micropuncture group had a significantly lower rate of hematoma than standard needle (32 [1.4%] vs. 309 [1.9%], p = .03). There was no significant difference in the rate of limb ischemia (1 [0.04%] vs. 12 [0.07%], p = .56), perforation (2 [0.08%] vs. 14 [0.09%], p = .93), retroperitoneal bleeding (3 [0.12%] vs. 18 [0.11%], p = .87), pseudoaneurysm (18 [0.76%] vs. 170 [1.09%], p = .14), and arteriovenous fistula (2 [0.08%] vs. 35 [0.22%], p = .16), comparing the Micropuncture group to a standard needle, respectively. Conclusions: Femoral access using a Micropuncture reduced the rate of vascular complications with significant reduction in the rate of groin hematomas.